2010
DOI: 10.1105/tpc.109.073726
|View full text |Cite
|
Sign up to set email alerts
|

Internal Architecture of Mitochondrial Complex I from Arabidopsis thaliana

Abstract: The NADH dehydrogenase complex (complex I) of the respiratory chain has unique features in plants. It is the main entrance site for electrons into the respiratory electron transfer chain, has a role in maintaining the redox balance of the entire plant cell and additionally comprises enzymatic side activities essential for other metabolic pathways. Here, we present a proteomic investigation to elucidate its internal structure. Arabidopsis thaliana complex I was purified by a gentle biochemical procedure that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
206
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(211 citation statements)
references
References 68 publications
5
206
0
Order By: Relevance
“…This suggests that ND4, ND5 and PSDW, on one hand, and ND1, ND3, ND4L, and ND6, on the other hand, are located in two different membrane domains of the complex I membrane arm. This hypothesis is in good agreement with structural models proposed for the localization of these subunits within for example Arabidopsis [9] or bovine complex I [49].…”
Section: Mutants Affected In Complex I or In Complexes I And Iiisupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that ND4, ND5 and PSDW, on one hand, and ND1, ND3, ND4L, and ND6, on the other hand, are located in two different membrane domains of the complex I membrane arm. This hypothesis is in good agreement with structural models proposed for the localization of these subunits within for example Arabidopsis [9] or bovine complex I [49].…”
Section: Mutants Affected In Complex I or In Complexes I And Iiisupporting
confidence: 89%
“…5 roles in regulation, protection against reactive oxygen species, assembly and stability [7]. In Arabidopsis, green algae and amoebozoa, subunits structurally related to gamma carbonic anhydrases have been found [6,8,9]. Single particle electron microscopy analyzes of complex I from Polytomella (a chloroplast-less and close relative of Chlamydomonas), A. thaliana, Zea mays and Solanum tuberosum indicate that these γ-CA subunits could constitute a spherical domain attached to the central part of the membrane arm of complex I, and exposed to the matrix (Fig.…”
Section: Main Components Of the Respiratory Chainmentioning
confidence: 99%
“…Although we cannot completely rule out the possibility that DNAJ/HSP40 and G3PD are non-mitochondrial contaminations of the mitochondrial fraction (see section 3 of Materials and Methods), our study brings evidence of a potential interaction between this cohort of proteins and respiratory CI. We recently proposed that some proteins might use CI as an anchoring point and that these interactions might be rather specific to limited groups or species (Cardol, 2011): acyl carrier protein (NDUFAB1/ACPM) and deoxyribonucleoside kinase-like subunit (NDUFA10/42 kDa) in mammals, galactono-lactone dehydrogenase in land plants (Klodmann et al, 2010), or rhodanese in Y. lipolytica (Angerer et al, 2011). Similarly, G3PD and DNAJ could be specifically associated with CI in E. gracilis.…”
Section: Complex Imentioning
confidence: 99%
“…Five proteins functioning in respiration, the cytochrome c oxidase At4g21105, the ubiquinol-cytochrome c reductase complex ubiquinone-binding protein At3g10860, and three components of mitochondrial complex I, At2g27730, At2g47690, and At4g20150 (Klodmann et al, 2010), showed increased abundance under Fe-deficient conditions (Table I; Fig. 4).…”
Section: Fe Deficiency Alters Respiration and Atp-coupled Transport Pmentioning
confidence: 99%